Seroprevalence of hepatitis E among restaurant food handlers in Ibadan, Nigeria (2019)
Background: Hepatitis E virus (HEV) is one of the causative agent of acute viral hepatitis in humans. HEV is an important public health disease in many parts of the world because it is transmitted faeco-orally. Majority of the documented studies on hepatitis E virus in Nigeria have focused on pregnant women and animal handlers with limited data among food handlers. Thus the current study aimed at investigating the prevalence of HEV infection among food handlers operating within the premises of a tertiary care facility. Methods: One hundred and seventy seven (177) food handlers were screened using commercial Enzyme- Linked Immuno-Sorbent Assay (ELISA) to detect IgM antibodies to Hepatitis E. A semi-structured questionnaire was used to assess risk factors for HEV infection. Results: HEV IgM antibodies were detected in 16 (9.0%) of the participants. Age-specific HEV IgM seroprevalence appeared to decrease with age, however there were no significant differences in HEV IgM seropositivity regarding age (P=0.251), gender (P = 0.231), marital status (P=0.735) and religion (P = 0.906). Significant risk factors for HEV IgM seropositivity included source of water for drinking (P=0.03) and the use of soap for hand washing (P=0.02). Conclusion: Our findings suggest that HEV remains a public health problem, as the virus circulates at low but considerable levels especially among food handlers; thus posing a threat to potential contacts. Proper hand washing practices as well as provision of portable water are important factors for the control of Hepatitis E.